The use of matrine to inhibit osteosarcoma cell proliferation via the regulation of the MAPK/ERK signaling pathway - Huang, Xincheng; Zeng, Jun; Ruan, Siyuan; Lei, Zhuolin; Zhang, Jingyuan; Cao, Hong (Frontiers in Oncology, 2024)
Background: Matrine is an alkaloid extracted from Sophorus beans of the legume family, and it has significant effects and a variety of pharmacological activities. Osteosarcoma(OS) is a common malignant bone tumor that is characterized by high incidence and rapid progression.There have been some preliminary studies on the therapeutic effect of matrine on OS, but the specific mechanism remains unclear.The aim of this study was to investigate the antitumor effect of matrine on HOS cells and the underlying molecular mechanism.The effects of matrine on the proliferation, apoptosis and cell cycle progression of HOS cells were determined by CCK-8 assay, TUNEL assay and flow cytometry in vitro. Wound healing and Transwell invasion assays were used to observe the effect of matrine on the migration and invasion of HOS cells. The mechanism underlying the antitumor effect of matrine on HOS cells was investigated by Western blotting.Results: Matrine significantly inhibited HOS cell proliferation, promoted HOS cell apoptosis, and arrested HOS cells in the G1 phase of the cell cycle. Both wound healing and Transwell invasion assays showed that matrine inhibited HOS cell migration and invasion. Western blotting results showed that matrine inhibited the activation of the MAPK/ERK signaling pathway. We found that matrine also downregulated Bcl-2 expression, which may be related to protein synthesis inhibition.Matrine can inhibit the proliferation of HOS cells, arrest HOS cells in the G1 phase, and promote HOS cell apoptosis through the MAPK/ERK signaling pathway.